2013
DOI: 10.1186/cc12784
|View full text |Cite
|
Sign up to set email alerts
|

The urine output definition of acute kidney injury is too liberal

Abstract: IntroductionThe urine output criterion of 0.5 ml/kg/hour for 6 hours for acute kidney injury (AKI) has not been prospectively validated. Urine output criteria for AKI (AKIUO) as predictors of in-hospital mortality or dialysis need were compared.MethodsAll admissions to a general ICU were prospectively screened for 12 months and hourly urine output analysed in collection intervals between 1 and 12 hours. Prediction of the composite of mortality or dialysis by urine output was analysed in increments of 0.1 ml/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 32 publications
(40 reference statements)
7
97
0
2
Order By: Relevance
“…In their analysis, a 6-hour urine output threshold of 0.3 ml/kg per hour yielded the optimal sensitivity and specificity for death or need for dialysis (61% and 77%, respectively). Our 3-hour urine output threshold of ,0.5 ml/kg per hour in a septic shock population had similar predictive power for stage II+ AKI, need for dialysis, and 28-day mortality (31).…”
Section: Discussionmentioning
confidence: 80%
“…In their analysis, a 6-hour urine output threshold of 0.3 ml/kg per hour yielded the optimal sensitivity and specificity for death or need for dialysis (61% and 77%, respectively). Our 3-hour urine output threshold of ,0.5 ml/kg per hour in a septic shock population had similar predictive power for stage II+ AKI, need for dialysis, and 28-day mortality (31).…”
Section: Discussionmentioning
confidence: 80%
“…They also appear to contrast with prior work by Ralib and colleagues, who found that the oliguria threshold of 0.5 ml/kg per hour was not predictive of survival, whereas 0.3 ml/kg per hour was. 5 These authors did not examine the effects of UO and SC together and their sample size was only 725 patients, limiting their statistical power. Other investigators have found UO to be a sensitive and early marker for AKI and to be associated with adverse outcomes in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In septic shock, a duration of at least 5 h, however, appears to be a good predictor of AKI [15]. Finally, Md Ralib et al [16] found a correlation between the volume of urinary output and duration of oliguria which suggested that a lower threshold of 0.3 ml/kg/h should be used, if the 6-hour observation interval is used as a minimum for the definition of stage of AKI. Also in the study from Koyner et al [17] patients with progressing AKI were mostly oliguric.…”
Section: Oliguria As Biomarkermentioning
confidence: 99%